Modes of Constructing Index-Numbers - Flux, A. W. (Quarterly Journal of Economics, 1907)
Journal Article Modes of Constructing Index-Numbers Get access A. W. Flux A. W. Flux McGill University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 4, August 1907, Pages 613–631, https://doi.org/10.2307/1883589 Published: 01 August 1907